Improvement in the Prediction of Summer Precipitation in the North China−Hetao Region Using the Tropospheric Temperature Over the Tibetan Plateau in Spring - Chen, Dan; Nan, Sulan; Liu, Ge; Zhou, Changyan; Shi, Renrui; Ao, Yinhuan; Li, Xiang (Frontiers in Earth Science, 2021)
We investigated the relationship between the spring tropospheric temperature over the Tibetan Plateau (TPT) and summer precipitation in eastern China on an interannual timescale using the monthly mean ERA-Interim reanalysis dataset, the HadISST dataset and the daily mean precipitation dataset for China. We found that there is a significant positive correlation between the spring TPT and summer precipitation in the North ChinaHetao region. The relationship is manifested in the context of the East Asia–Pacific pattern teleconnection. In the high spring TPT index years, the geopotential height anomalies over East Asia and the western North Pacific present a negative phase of the East Asia–Pacific pattern teleconnection in the subsequent summer. The circulation pattern favors the transport of water vapor inland from the western Pacific and results in a divergence of precipitation from the region of the Yangtze–Yellow rivers to the North ChinaHetao region. Anomalous upward motion occurs in the North China–Hetao region, which increases precipitation. The East Asian subtropical westerly jet shifts further north and the South Asian high weakens and shrinks westward. These conditions all favor an increase in precipitation over the North China–Hetao region. The spring TPT plays an important part in the prediction of summer precipitation in the North ChinaHetao region. The improvement in the use of the spring TPT to predict summer precipitation in the North China–Hetao region is examined by comparing the prediction equations with and without the prediction factor of the spring TPT on the basis of the sea surface temperatures in key regions. After considering the impact of the spring TPT, the explanatory variance of the prediction equation for precipitation in the North China–Hetao region increases by 17.3%.